Review of the accreditation of digital forensics in China - Hong Guo; Junlei Hou (Oxford University Press, 2018)
As a result of the many developments in information technology, digital evidence plays an increasingly important role in criminal and civil litigation. Because digital evidence is necessary for litigation, the judicial system must be assured of its accuracy, reliability, and verifiability, which can be assured by accreditation. This paper focuses on a comparison of the evolution of the accreditation of digital forensics internationally and domestically, discusses the existing problems that such accreditation encounters, and proposes the corresponding solutions. Moreover, this paper discusses the future of digital forensic laboratory accreditation and its implementation.